Difference limens of amplitude modulated signals - OZIMEK, Edward; SĘK, Aleksander (Archives of Acoustics, 1987)
Presented in the literature studies on the perception of amplitude modulated signals concentrate mainly on the determination of modulation thresholds, and of the so-called roughness and amplitude of a signal. Whereas papers concerned with difference limens of amplitude modulation of carriers more complex than a tonal signal are lacking. With this in mind, research aimed in principle at the determination of difference limens of noise octave bands amplitude modulated with sinusoidal signals was undertaken. A comparison of these limens with values of STI which is an objective measure of speech intelligibility in a room was another important aim of performed studies. Such a comparison was a certain psychoacoustic verification of the perception ability of definite changes of the STI by a listener. Research results proved that difference limens depend significantly on the modulation factor of the reference signal. It was also found that difference in the STI values, determined with the objective method (the so-called RASTI method), which determine room quality from the point of view of speech intelligibility are found in the range of difference limens of amplitude modulated signals or below these limens.